AGON AS AN IMMANENT CHARACTERISTIC FEATURE OF ANCIENT GREEK CULTURE - Evgeny Y. Rezhabek; Marina A. Bogdanova (Advanced Engineering Research, 2011)
The thesis of agonality as the fundamental characteristic of the Classical Greek culture is supported in the article. Competitiveness as the system-forming principle of the Greek society penetrates all spheres of the social life. Acquisition of high status by agonality is connected with the Greek cognitive peculiarities.